Inovação, competição internacional e transição hegemônica: a política científico-tecnológica dos Estados Unidos para evitar o declínio no século XXI - Moreira Júnior, Hermes [UNESP] (2015)
The financial crisis that hit the center of international economic system reinforced the debates on world order and the perspectives about the transition of hegemonic center in the constitution of a new order. In response to this scenario, the US government, with Barack Obama, stimulated the recovery process of their innovative industry, supported by the conviction that the maintenance of the international leadership, with consequent design setting capacity of the world order is related to the higher level of competitiveness and industrial productivity of the country. This thesis aims evaluate the Obama administration's national innovation strategy within the institutional path that led the US scientific and technological policy during the twentieth century. Innovation trajectories are affected to critical junctures in the national and international economy. The current financial crisis offered conditions for changes in the innovation model adopted during the 1980s, in the context of financialization of the global economy and lack of interventionist role of the state in the US economy. Model whose aftermath was the expansion of the private risk capital to innovation research and the market's autonomy to set priority sectors. In this sense, from the literature review on national innovation systems, and analysis of scientific and technological policy proposed by the federal government, this thesis demonstrates that Obama administration seeks re-establish a scientific and technological policy aimed at innovation in which the state is responsible for defining the strategic sectors to be prioritized by the national innovation system, according to national challenges to be faced in the context of international competition.